Metal‐Insulator Transition in ALD VO2 Ultrathin Films and Nanoparticles: Morphological Control. (15th December 2014) - Peter, Antony P.; Martens, Koen; Rampelberg, Geert; Toeller, Michael; Ablett, James M.; Meersschaut, Johan; Cuypers, Daniel; Franquet, Alexis; Detavernier, Christophe; Rueff, Jean‐Pascal; Schaekers, Marc; Van Elshocht, Sven; et al.
<x xml:space="preserve">Abstract</x> Nanoscale morphology of vanadium dioxide (VO2) films can be controlled to realize smooth ultrathin (<10 nm) crystalline films or nanoparticles with atomic layer deposition, opening doors to practical VO2 metal‐insulator transition (MIT) nanoelectronics. The precursor combination, the valence of V, and the density for as‐deposited VO2 films, as well as the postdeposition crystallization annealing conditions determine whether a continuous thin film or nanoparticle morphology is obtained. It is demonstrated that the films and particles possess both a structural and an electronic transition. The resistivity of ultrathin films changes by more than two orders of magnitude across the MIT, demonstrating their high quality.